2023
DOI: 10.1002/bmc.5597
|View full text |Cite
|
Sign up to set email alerts
|

A simple and sensitive LC–MS/MS method for the determination of polyphyllin VII in rat plasma and its application to pharmacokinetic study

Abstract: Polyphyllin VII is an isoprene saponin extracted from Rhizoma paridis, and it can effectively suppress tumor initiation, growth, and metastasis. In this study, we aim to develop and validate an LC-MS/MS method for the quantification of polyphyllin VII in rat plasma using digoxin as the internal standard (IS). The plasma samples were precipitated with methanol, and the samples were separated on an ACQUITY BEH C 18 column (2.1 Â 50 mm, 1.7 μm). The mobile phase consisted of 0.1% formic acid solution and acetonit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…At an in vivo dose of 1/20 of LD 50 (2 mg/kg), PPVII had no significant effect on the liver, spleen, and kidney functions of nude mice, which indicated that PPVII had little toxicity in vivo. According to our previous papers and other reports about the pharmacokinetic data of PPVII in SD rats, the bioavailability of oral administration of PPVII is much lower than that of intraperitoneal administration, and has low gastrointestinal absorption or overhead metabolic problems (H. Wang et al, 2023). Thus, current animal study only used one mode of intraperitoneal injection.…”
Section: Discussionmentioning
confidence: 99%
“…At an in vivo dose of 1/20 of LD 50 (2 mg/kg), PPVII had no significant effect on the liver, spleen, and kidney functions of nude mice, which indicated that PPVII had little toxicity in vivo. According to our previous papers and other reports about the pharmacokinetic data of PPVII in SD rats, the bioavailability of oral administration of PPVII is much lower than that of intraperitoneal administration, and has low gastrointestinal absorption or overhead metabolic problems (H. Wang et al, 2023). Thus, current animal study only used one mode of intraperitoneal injection.…”
Section: Discussionmentioning
confidence: 99%